TEACHING READING NARRATIVE TEXT THROUGH ONLINE READING STRATEGY - Fitri Novia; Ratna Nery; Indah Lestari (Relawan Jurnal Indonesia, 2023)
The objective of this study was to find out whether or not there was a significant difference in reading comprehension achievement between the eighth grade students of SMP PGRI Pedamaran who were taught using the Online Reading Strategy and those who were not. Quasi-experimental method was used in this study. To collect data, a written test was in the form of multiple choice questions. The test was tried out in order to find out the reliability of the test. Before analyzing the data, normality and homogeneity were found. To analyze the data, t-test was used. Based on the results of the independent sample t-test, it was found that the t-test obtained (2.917) was higher than the t-table (2.00) and the Pvalue (0.000) was less than ɑ value (0.05). It showed that null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. It meant that there was a significant difference in reading comprehension achievement between the students who were taught by using Online Reading Strategy and those who were not. In other words, online reading strategy improved the reading comprehension achievement of eighth graders of SMP PGRI Pedamaran.